Lifestyle and Struggle of the Nomadic Nat Community: A study of the Nat community in Sarlahi, Nepal - Shrestha, Laxman (International Research Journal of MMC, 2022)
The Nat community, which involves the people of a Madheshi Dalit caste, comprises a nomadic lifestyle and history. The main objective of this study is to investigate the lifestyle, history, citizenship, ownership of property, profession, religion, education and usage of information technology of the nomadic community with permanent residence. In this research, descriptive and explanatory research framework has been adopted. Data were collected through in-depth interviews using qualitative and quantitative methods and household survey methods. Historical and frequency analysis were adopted to analyze data. Information and data were collected through in-depth interviews with 47 respondents using a semi-structured questionnaire. This study reveals that lifestyle and occupation of Nat community were closely related with their poor educational status. Out of 47 participants of this community, 45 had got Nepali citizenship. It was found that 43 of the 47 participants had their own house. It has been found that the main occupations of all 47 respondents were begging. Out of total, 58 percent of school age children were out of school and the school going children scarcely went to school. With their nomadic lifestyle and begging occupation, they appeared be in the primitive hunter-gatherer stage of human social development. Due to the lifestyle of the Nat community, they were found to be illiterate, poor and marginalized.